2011
DOI: 10.1038/jcbfm.2011.99
|View full text |Cite
|
Sign up to set email alerts
|

Interendothelial Claudin-5 Expression Depends on Cerebral Endothelial Cell–Matrix Adhesion by β1-Integrins

Abstract: The hypothesis tested by these studies states that in addition to interendothelial cell tight junction proteins, matrix adhesion by b 1 -integrin receptors expressed by endothelial cells have an important role in maintaining the cerebral microvessel permeability barrier. Primary brain endothelial cells from C57 BL/6 mice were incubated with b 1 -integrin function-blocking antibody (Ha2/5) or isotype control and the impacts on claudin-5 expression and microvessel permeability were quantified. Both flow cytometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
120
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(127 citation statements)
references
References 39 publications
6
120
0
Order By: Relevance
“…32 Bearing HG-induced cytoskeletal reorganization in mind, possible changes exerted on HBMEC-matrix interactions regulated via b1-integrin may also contribute to barrier permeability by directly affecting claudin-5 expression as recently reported. 33 In conclusion, the current study demonstrates that activations of PKC-b or RhoA/Rho-kinase/p-MLC2 pathway under hyperglycemic conditions mediate the structural and functional impairment of an in vitro model of human cerebral barrier. Considering the regulatory effects of PKC-b on the expression, phosphorylation, and/or activity of RhoA/Rho-kinase/p-MLC2 pathway components and organization of cytoskeleton and TJ assembly, it is plausible to suggest that PKC-b may be an efficacious novel therapeutic target to stem the cerebral barrier dysfunction in hyperglycemic stroke.…”
Section: Discussionmentioning
confidence: 54%
“…32 Bearing HG-induced cytoskeletal reorganization in mind, possible changes exerted on HBMEC-matrix interactions regulated via b1-integrin may also contribute to barrier permeability by directly affecting claudin-5 expression as recently reported. 33 In conclusion, the current study demonstrates that activations of PKC-b or RhoA/Rho-kinase/p-MLC2 pathway under hyperglycemic conditions mediate the structural and functional impairment of an in vitro model of human cerebral barrier. Considering the regulatory effects of PKC-b on the expression, phosphorylation, and/or activity of RhoA/Rho-kinase/p-MLC2 pathway components and organization of cytoskeleton and TJ assembly, it is plausible to suggest that PKC-b may be an efficacious novel therapeutic target to stem the cerebral barrier dysfunction in hyperglycemic stroke.…”
Section: Discussionmentioning
confidence: 54%
“…There are two basement membranes at the BBB: the vascular basement membrane secreted by BECs and pericytes, and the glial basement membrane secreted by astrocytes. The ECM provides structural support for the vessels, a scaffold for growth factors such as PDGF-BB, VEGF, TGF-β, as well as providing a physical barrier for leukocyte migration into the parenchyma.The basement membrane also regulates BBB permeability.Osada et al demonstrated that endothelial cell adhesion to the ECM by β 1 -integrins increases CLDN-5 expression(Osada et al, 2011). Moreover,Menezes et al observed that Lama2-null mice display an increase in BBB permeability compared to wildtype littermates which correlated with a lower pericyte and astrocytic endfeet coverage, a lower expression of VE-cadherin, Cldn-5 and occludin and an increase of PLVAP expression(Menezes et al, 2014).…”
mentioning
confidence: 99%
“…We sorted genes that were increased over 2-fold in the MCAO group compared with normal group, then screened for genes that were down-regulated more than 2-fold in the si-ASK1 group compared with the MCAO group. Several genes were selected, including matrix metallopeptidase 3 (MMP3) (Ashina et al, 2010), integrin alpha 8 (Itga8) (Cucullo et al, 2011;Osada et al, 2011), cadherin 1 (Cdh1) (Zechariah et al, 2013), gap junction protein beta 1 (Gjb3) (Song et al, 2007), Selectin (Sele) (Jin et al, 2010), intercellular adhesion molecule 1 (Icam1) (An and Xue, 2009), aquaporin 8 (Aqp8) (Richard et al, 2003), aquaporin 12 (Aqp12) (Calvanese et al, 2013) related with vascular permeability. Also, vascular endothelial growth factor A (Vegfa) (Gong et al, 2014;Poittevin et al, 2014), and vascular endothelial growth factor C (Vegfc) (Foster et al, 2008;Xu et al, 2013) which are related with vascular permeability were down-regulated in the si-ASK1 group compared with the MCAO group slightly.…”
Section: Resultsmentioning
confidence: 99%